Introduction to statistics for forensic scientists - Lucy David (Chichester John Wiley, 2005)
Opening with a brief overview of the history and use of statistics within forensic science, the text then goes on to introduce statistical techniques commonly used to examine data obtained during laboratory experiments. There is a strong emphasis on the
Keywords: Applied statistics; Evidence(Law)-statistical methods; Forensic sciences; Forensic statistics